Use of Standard Deviations as Predictors in Models Using Large-Scale International Data Sets. Issue 4 (2nd October 2017) - Austin, Bruce; French, Brian; Adesope, Olusola; Gotch, Chad
ABSTRACT: Measures of variability are successfully used in predictive modeling in research areas outside of education. This study examined how standard deviations can be used to address research questions not easily addressed using traditional measures such as group means based on index variables. Student survey data were obtained from the Organisation for Economic Co-operation and Development to examine standard deviation predictors in multilevel models. These predictors and interactions explained additional variation in the dependent variable beyond the control variables. Models using biased and unbiased standard deviations were compared. Meaningful differences were found between the models. Findings supported how standard deviation predictors may increase explanatory power and accuracy of models commonly used in educational research.